Sulitnya Regenerasi Petani pada Kelompok Generasi Muda - Rahmat Saleh; Irin Oktafiani; Marya Yenita Sitohang (Universitas Gadjah Mada, 2021)
Youth generation in the agrarian sector is needed to maintain food production and the possibility of discovering or developing new technologies. This article aims to describe the development of studies on farm children's existence, especially in Indonesia, and why many have decided not to become farmers. This article uses a qualitative research approach based on digital methods. Data were obtained through a literature review of 42 journal articles from previous research regarding children and young people in farming families. All data collected was processed using NVivo software. The findings of this study indicate that farmer regeneration in Indonesia faced various complex problems. Children's education factors, including dropping out of school, access to limited land, poverty, and migration activities, dominate the difficulty of regenerating farmers in farming families. This article also shows the need for intervention from various parties to support increased food security.